Penerapan Metode Design thinking Pada Pengembangan Knowledge Management System Pembelajaran SMA - Damayanti, Indri Dwi; Firdaus, Afriyan; Indah, Dwi Rosa (Jurnal Teknik Informatika dan Sistem Informasi, 2023)
High school learning requires teachers to carry out the teaching process using appropriate learning methods and materials based on expected competencies. At SMA IBA Palembang, knowledge and experiences possessed by the teacher are still stored in each teacher and have not been documented in a system. However, when a teacher retires, the knowledge and experiences of the teacher will also go away and be lost. Therefore a Knowledge Management System (KMS) to manage teacher knowledge needs to be developed. In order to improve KMS development results in terms of usability and user experience, user experience design with the Design Thinking Method is an option. In this paper KMS development with the Design Thinking Method is used to identify problems and existing user needs. This solution can produce good user interface and user experience based on user needs at SMA IBA Palembang. Before being implemented, the KMS has been tested using the System Usability Scale method with an average value of 81.43. It means that the system is accepted by prospective users. The KMS implementation was tested with 43 test items using the Blackbox Testing method. The result stated that the system could function to solve problems that occurred.